2022
DOI: 10.1073/pnas.2201513119
|View full text |Cite
|
Sign up to set email alerts
|

The doublesex gene regulates dimorphic sexual and aggressive behaviors in Drosophila

Abstract: Most animal species display dimorphic sexual behaviors and male-biased aggressiveness. Current models have focused on the male-specific product from the fruitless ( fru M ) gene, which controls male courtship and male-specific aggression patterns in fruit flies, and describe a male-specific mechanism underlying sexually dimorphic behaviors. Here we show that the doublesex ( dsx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…TN1 neurons are one of the anatomically distinct dsx-expressing neuronal clusters 22,26 , allowing the quantification of TN1 cell number by probing dsx mRNA or protein. Both in situ hybridization chain reaction (HCR) 27,28 using dsx mRNA probes and immunostaining (IHC) using Dsx antibodies 29 confirmed the presence of a TN1 cluster in D. yakuba, but with ~10 fewer neurons than in D. melanogaster (Fig. 1c).…”
Section: Yakuba Has Fewer Sine-song-essential Tn1 Neuronsmentioning
confidence: 77%
“…TN1 neurons are one of the anatomically distinct dsx-expressing neuronal clusters 22,26 , allowing the quantification of TN1 cell number by probing dsx mRNA or protein. Both in situ hybridization chain reaction (HCR) 27,28 using dsx mRNA probes and immunostaining (IHC) using Dsx antibodies 29 confirmed the presence of a TN1 cluster in D. yakuba, but with ~10 fewer neurons than in D. melanogaster (Fig. 1c).…”
Section: Yakuba Has Fewer Sine-song-essential Tn1 Neuronsmentioning
confidence: 77%
“…It has been found that female pC1 neurons could be divided into subtypes at the single-cell level[19], and different pC1 subtypes regulated sexual and aggressive behaviors, respectively[17, 19, 20]. We propose that distinct pC1 subsets may have different activation thresholds to hierarchically control multiple behaviors.…”
Section: Resultsmentioning
confidence: 93%
“…RNAi lines were from Tsinghua Fly Center (THFC) at the Tsinghua University. UAS-FRT-stop-FRT-dTrpA1 [34], UAS-FRT-stop-FRT-TNT in , UAS-FRT-stop-FRT-TNT [61], dsx GAL4 , dsx LexA and dsx DBD [20] were used as previously. The full genotypes of tested flies are described in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of aggression towards a wingless male parallels observations that P1a neuron activation selectively triggers courtship towards inanimate visual targets 38,[40][41][42] , highlighting the importance of sensory and behavioral feedback cues in shaping a male's ongoing actions. We therefore searched for additional circuit nodes sufficient to drive wing flicks, focusing on neurons marked by expression of the Doublesex transcription factor due to its role in specifying sexually-dimorphic patterns of aggression [72][73][74][75][76] . We identified a previously described intersectional genetic driver, pC1-SS2 14,77 , that labels four neurons within the central brain as a potential candidate (Figures 6E, S9A-C).…”
Section: Male-male Interactions Regulate Mating Successmentioning
confidence: 99%